„Królowa chaosu, niezrównoważona emocjonalnie, histeryczka trzaskająca drzwiami” – leksykalne sposoby wartościowania w tekstach prasowych poświęconych Ewie Kopacz (na materiale wybranych tygodników opinii z września 2014 roku) - Budzyńska-Łazarewicz, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
Is to present lexical ways of evaluation, which are present in press articles dedicated to the election of E. Kopacz for prime minister. The study material consists of articles published in eight public opinion weeklies, which were published in Poland in September of 2014. They are journals with different ideological profiles. Among the noted lexical terms, there are primarily-evaluative as well as descriptively-evaluative expressions. These are adjectives, adverbs, participles, pronouns and modality indicators. Numerously represented are statements in which the authors report affirmations that evaluate other people. The analysed terms invoke, most of all, the utilitarian, perfectionist, cognitive, socially-custom criterion. Among the noted terms, the majority consists of those with a negative value mark. As it turned out, the ideological engagement of periodicals had a slight impact on the media image of E. Kopacz. An almost solely negative evaluation was present in conservative press. However, the press, which can be described as liberal, also pointed the weaknesses of the new prime minister, recalling negative opinions about her. It did it, however, in a more veiled manner.